2019
DOI: 10.1002/brb3.1462
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum creatinine/cystatin C in neurocritically ill patients

Abstract: ObjectiveTo explore the predictive value of serum creatinine (Cr) to cystatin C (CysC) ratio in neurocritically ill patients.MethodsWe conducted a retrospectively observational study of adult patients admitted to a neurocritical care unit (NCU) between Jan 2013 and Jan 2017. Patients were excluded if <18 years old, required neurocritical care <72 hr, did operation during hospitalization, had premorbid disability or acute kidney injury (AKI) at admission. The Cr/CysC ratio was obtained at NCU admission. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…( 13 15 ) Furthermore, Cre/Cys ratio correlated with muscle strength ( 28 ) and predicted prognostic outcomes in various diseases, including hepatocellular carcinoma. ( 29 33 ) However, to the best of our knowledge, the association between Cre/CysC ratio and sarcopenia in NAFLD has never been reported. Thus, our study is the first to show a positive relationship between Cre/CysC ratio and both muscle mass and muscle strength in NAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…( 13 15 ) Furthermore, Cre/Cys ratio correlated with muscle strength ( 28 ) and predicted prognostic outcomes in various diseases, including hepatocellular carcinoma. ( 29 33 ) However, to the best of our knowledge, the association between Cre/CysC ratio and sarcopenia in NAFLD has never been reported. Thus, our study is the first to show a positive relationship between Cre/CysC ratio and both muscle mass and muscle strength in NAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…7 By contrast, an indicator that can be easily calculated that reflects SMM simply is the serum creatinine/serum cystatin-C ratio, the so-called sarcopenia index (SI). Studies have also been published suggesting that low SI can predict poor long-term prognosis in noncardiac conditions such as neuro critically ill patients, 8 acute kidney injury (AKI) requiring renal replacement therapy (RRT) 9 and cardiovascular procedures including postpercutaneous coronary intervention (PCI). 10 However, the clinical relevance of SI in older patients undergoing TAVR has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that higher creatinine-tocystatin C ratio at baseline was associated with better prognostic outcomes including low risk of cardiovascular events 23,24 and short-and long-term mortality. [25][26][27] However, none of them has assessed whether changes in creatinine-to-cystatin C ratio were predictive for future health outcome. As an attempt to fill in this blank, our study showed that both absolute and relative increases in creatinine-to-cystatin C ratio during follow-up were related to reduced risk of diabetes.…”
Section: Interpretationsmentioning
confidence: 99%